Investigation of the mechanic behaviours in hollow composite shafts having different fiber reinforcement and orientation angles - Yildirim, H.; Pihtili, H. (Wiley-V C H Verlag Gmbh, 2016)
This study experimentally investigates the mechanical properties and behaviors of the hollow circular composite shafts, which are widely used in the industry and operated under a variety of environmental influences. Within the context of this study, glass, carbon and kevlar fibers were utilized as fiber materials and epoxy resins were preferred as the matrix material for hollow circular composite shafts. Composite shafts having 80 mm, 200 mm, 250 mm length and different internal diameters were used for three-point bending tests. Composite hollow shafts were manufactured by utilizing filament winding method at different orientation angles (theta = 45 degrees, 60 degrees, 75 degrees, 80 degrees, 88 degrees). The bending behaviors of the hollow circular composite shafts manufactured were repeated separately for each sample in three-point bending tests. The results obtained were evaluated inter se, displayed in graphics and necessary considerations were addressed.
Untersuchung des mechanischen Verhaltens von Hohlwellen aus Verbundwerkstoffen mit unterschiedlichen Faserverstärkungen und -winkelorientierungen
Keywords: Composite shafts; Filament winding; Orientation angle; Three-point bending test